NON-FUNCTIONAL SHOPPING MOTIVES AMONG IRANIAN CONSUMERS - Shahriar AZIZI; Amir SHARIFFAR (Management & Marketing)
This study aims to explore the non functional shopping motives among Iranian consumers. In addition, the effects of marital status, gender, age and residential region as an indicator for social class on the non-functional shopping motives are investigated. This paper uses a self-reported and 15 items questionnaire. The analysis is done based on 363 returned and usable questionnaires. Multivariate analysis of variance is applied for this study. MANOVA results show that marital status, gender, age and region have different significant effects on the non-functional shopping motives among Iranian consumers.